Inserting Tropical Dry Forests Into the Discussion on Biome Transitions in the Tropics - Dexter, Kyle G.; Pennington, R. Toby; Oliveira-Filho, Ary T.; Bueno, Marcelo L.; Silva de Miranda, Pedro L.; Neves, Danilo M. (Frontiers in Ecology and Evolution, 2018)
Tropical moist forests and savannas are iconic biomes. There is, however, a third principal biome in the lowland tropics that is less well known: tropical dry forest. Discussions on responses of vegetation in the tropics to climate and land-use change often focus on shifts between forests and savannas, but ignore dry forests. Tropical dry forests are distinct from moist forests in their seasonal drought stress and consequent deciduousness and differ from savannas in rarely experiencing fire. These factors lead tropical dry forests to have unique ecosystem function. Here, we discuss the underlying environmental drivers of transitions among tropical dry forests, moist forests and savannas, and demonstrate how incorporating tropical dry forests into our understanding of tropical biome transitions is critical to understanding the future of tropical vegetation under global environmental change.